MDR PATIENT AND DM WITH CAVITARY FUNGUS BALL DUE TO HAEMOPTOE RECURRENT: A CASE REPORT - Pakpahan, Edwin Anto; Pratiwi, Annisa Nola; Putri, Frisca Indriani; Harahap, Putri Yana; Gunawan, Qibran Aziz; Siregar, Anandya Annisa Amri (Majalah Ilmiah METHODA, 2023)
A 53-year-old man was admitted to Drs. H. Amri Tambunan Hospital with complaints of extreme weakness since today, coughing up blood was found 3 days every time he coughed. Right chest pain like stabbing is found 4 days. Nausea is found 3 days, vomiting is found just today, the contents of what is eaten, decreased appetite and weight are found. The patient is currently taking MDR anti-tuberculosis drugs. Physical examination showed chest wall retraction, weak peristalsis in the abdomen. Thorax examination revealed right Koch Pulmonum or right pulmonary TB with right Aspergillosis/fungus ball of right superior lobe. Lab examination showed that the patient was diabetic. Surgical lobectomy was performed to find a mass of 3 cm in diameter, white-white grey-brown in color, spongy in consistency. The diagnosis of aspergilloma was confirmed by microscopic examination. Tuberculosis and type 2 DM have impaired immunity due to insulin resistance, this is exacerbated by malnutrition which results in ineffective absorption of anti-tuberculosis drugs. This condition makes patients susceptible to fungal infections such as Aspergillus sp. Patients need to maintain blood glucose levels and improve nutritional status to improve their treatment prognosis. Lobectomy surgery on the superior lobe of the right lung also promotes a better prognosis in treatment.